Evaluation of permanent premolars intended for endodontic treatment in term of root number & form, condition of periapical area and state of lamina dura (Radiographic survey). (Mustansiria Dental Journal, 2018)
The radiographic film serves an extremely important need in detecting disease process that affects the tooth and its surrounding structures. The aim of the present study is to take a radiographic view to determine root number and form, condition of the periapical area and state of the lamina dura for permanent premolar teeth intended for root canal therapy. One hundred ninety radiographs representing the step of working length determination for permanent premolars intended for root canal therapy were selected from a number of private clinics in Baghdad. Results of this study shows that 52.1 % of the endodontically treated teeth having curvature free roots, while 47.9 % of them were presented with curved roots, most of teeth 94.2% were free of periapical lesions and lamina dura was absent in 65.8 % of the teeth.